2015
DOI: 10.3109/10428194.2014.996751
|View full text |Cite
|
Sign up to set email alerts
|

Induction of TAp73 by platinum-based compounds to overcome drug resistance in p53 dysfunctional chronic lymphocytic leukemia

Abstract: In chronic lymphocytic leukemia (CLL), strategies to overcome drug resistance due to p53 dysfunction are highly needed. Platinum-based compounds such as cisplatinum (CDDP) are active in fludarabine-refractory CLL through a largely unknown mechanism. We analyzed the mechanism of action of CDDP in the context of p53 dysfunctionality. In vitro treatment with CDDP did not induce death in quiescent CLL cells, but did induce apoptosis in CD40-ligand (and CpG) stimulated and proliferating cells, irrespective of p53 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
(57 reference statements)
0
5
0
Order By: Relevance
“…Because of the urgent treatment indication and because as of today no established effective salvage remission-induction treatment before alloSCT is available, we chose R-DHAP based on promising clinical and in vitro data. 20,23,36,37 R-DHAP resulted in remission or SD in the majority of patients of whom almost all subsequently proceeded to alloSCT (patients with progressive disease were not transplanted according to the protocol). The total treatment sequence of R-DHAP and alloSCT (only for those with at least stable disease after R-DHAP, a suitable medical and physical condition and the availability of a donor) resulted in a 2-year PFS of 42% (95% CI 27-56%), while based on literature before the use of targeted agents, a 2-year PFS of 25% was expected without alloSCT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the urgent treatment indication and because as of today no established effective salvage remission-induction treatment before alloSCT is available, we chose R-DHAP based on promising clinical and in vitro data. 20,23,36,37 R-DHAP resulted in remission or SD in the majority of patients of whom almost all subsequently proceeded to alloSCT (patients with progressive disease were not transplanted according to the protocol). The total treatment sequence of R-DHAP and alloSCT (only for those with at least stable disease after R-DHAP, a suitable medical and physical condition and the availability of a donor) resulted in a 2-year PFS of 42% (95% CI 27-56%), while based on literature before the use of targeted agents, a 2-year PFS of 25% was expected without alloSCT.…”
Section: Discussionmentioning
confidence: 99%
“…21 In vitro studies demonstrated that platinum-based compounds induce TP53-independent cell death of CLL cells from chemorefractory CLL patients. 22,23 Rituximab was added to the DHAP chemotherapy backbone as it appeared to be of additive value in the relapsed setting when combined with chemotherapy. 24,25 …”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the cytotoxicity of these drugs on mut-p53 cell lines was significantly higher than wt-p53 cell lines, this is consistent with the recent research which showed that cancer cells with p53 mutations might retain residual function in relation to cell death activity and respond better to anticancer therapy than p53 null mutations [ 25 ]. However, p53 mutation is part of the cause of CIS resistance [ 26 ], and p53 gene mutations occur in more than 80% of ESCC, thus, find a concomitant medication to reduce the toxicity of CIS and improve its efficacy is particularly important. Fortunately, in the current study, CIS plus ORI showed a promising synergistic effect on mut-p53 cell lines when compared with their effect on wt-p53 cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Platinum-based drugs (cisplatin, oxaliplatin, etc.) help the cell overcome drug resistance by increasing activity of the TAp73 protein and inducing the apoptosis of tumor cells [ 118 ]. In addition, cisplatin suppresses the pro-oncogenic form ΔNp63α, which can also inhibit tumor growth [ 119 , 120 ] and presumably enhance its radiosensitivity.…”
Section: Ways To Overcome Radioresistance Upon Modulation Of P53-family Proteinsmentioning
confidence: 99%